(untitled) (Fiep Bulletin - online, 2013)
Equine therapy is a therapeutic method that makes the use of horses to rehabilitate patients suffering from cerebral palsy toward shaping muscular tone, enhancing posture, and to improving movement and posture control of automatic actions. Cerebral Palsy is a condition derived from encephalic aggression on posture and movement characterized by muscle tension alterations that manifests early in life. This research is a bibliographic exploratory study of analytical and descriptive character relying with the contribution of many authors. It is of qualitative nature with the purpose of analyzing the effects of Equine therapy in patients suffering from Cerebral Palsy. Six articles, a master`s thesis, and two pornographies published between 1998 and 2008 were analyzed. After descriptive analysis it is possible to assert that Equine therapy exerts different affects in patients suffering from Cerebral Palsy, such as: development of self steam, dependability, discipline, concentration, well being, improvement of social relationships, motor coordination, upper body and stiffness and muscular tone, as well as posture control.